Relationship between left ventricular mechanical dyssynchrony and accelerated 99mTc-MIBI clearance in patients with heart failure - A. I. Mishkina; T. A. Atabekov; S. I. Sazonova; S. V. Agafonkin; R. E. Batalov; K. V. Zavadovsky (Российский кардиологический журнал, 2024)
Aim. To evaluate 99mTc-methoxy-isobutyl-isonitrile (99mTc-MIBI) washout rate and its relationship with contractility and left ventricular (LV) mechanical dyssynchrony in patients with heart failure (HF) of non-ischemic origin.Material and methods. The study included 20 patients with HF of non-ischemic origin with indications for cardiac resynchronization therapy (CRT). Ten patients without HF were included in the comparison group. All patients underwent 99mTc-MIBI myocardial perfusion scintigraphy (MPS). We assessed the 99mTc-MIBI washout rate, as well as LV perfusion, contractility, and mechanical dyssynchrony using phase analysis data (phase standard deviation, histogram bandwidth (HBW), asymmetry, and gradient). Six months after CRT, all patients with HF underwent MPS to assess the changes of studied parameters.Results. According to MPS, patients with HF had a higher 99mTc-MIBI washout rate from the LV myocardium compared with the comparison group (10,9 (8,49-13,8) vs 3,98 (0,9-9,8)%, p=0,0001), as well as severe LV mechanical dyssynchrony (standard deviation: 66 (55,11-73,24) vs 13,1 (10,1-19,6), p<0,0001; HBW: 207 (165-246) vs 40 (33-66), p<0,0001). The 99mTc-MIBI washout rate was positively correlated with LV end-diastolic (r=0,46, p<0,001) and LV end-systolic volumes (r=0,44, p<0,001) and negatively correlated with LV ejection fraction (r=0,41, p<0,001). A moderate correlation was found between the 99mTc-MIBI washout rate and following LV mechanical dyssynchrony and contractility parameters: HBW (r=0,412, p<0,001), asymmetry (r=-0,41, p<0,001), gradient (r=-0,44, p<0,001), wall motion (r=-0,45, p=0,001), wall thickening (r=-0,54, p<0,001). Six months after CRT, all patients showed a significant decrease in the 99mTc-MIBI washout rate from 12,4 (10,3-14,9) to 8,14 (3,37-8,88)%, p=0,0006.Conclusion. In patients with HF of non-ischemic origin, an increase in the 99mTc-MIBI washout rate from the LV myocardium is associated with the severity of impaired cardiac contractility and mechanical dyssynchrony.